Temporomandibular joint positional change accompanies post‐surgical mandibular relapse—A long‐term retrospective study among patients who underwent mandibular advancement. (7th December 2017) - Miao, M. Z.; Wang, B.; Wu, D.; Zhang, S.; Wong, S.; Shi, O.; Hu, A.; Mao, L.; Fang, B.
Structured Abstract: Objective: This study evaluated the relationship between follow‐up temporomandibular joint positional change and mandibular stability among patients who had orthognathic and orthodontic treatment for a skeletal Class II malocclusion. Methods: Thirty‐seven patients who underwent 2‐jaw surgery (Le Fort I osteotomy, bilateral sagittal split ramus osteotomy and genioplasty with rigid internal fixation) were included with an average follow‐up length of 8.10 ± 2.06 years. They were categorized into a stable and unstable group according to follow‐up mandibular change in the sagittal direction. Temporomandibular joint spaces were measured on serial magnetic resonance images, prior to orthodontic treatment (T0), upon completion of orthodontic treatment following surgery (T1), and at least 5 years post‐completion of the treatment (T2). Results: While the maxillary position was stable during the follow‐up period, the mandibular positional change was statistically significant (the relapse amount was −0.81 ± 1.52 mm at B point). An increase in the anterior joint space and superior joint space was found to correlate with the follow‐up mandibular backward movement. Conclusions: Patients who underwent orthognathic and orthodontic treatment to correct mandibular retrognathism displayed follow‐up mandibular relapse in the sagittal direction. The relapse is accompanied by condylar positional change.